2018
DOI: 10.18291/njwls.v8i3.109540
|View full text |Cite
|
Sign up to set email alerts
|

Hiring of Flexible and Fixed-term Workers in Five Norwegian and Swedish Industries

Abstract: Analyzing how and why employers use fixed-term contracts or alternative forms of flexible, shortterm labor in five labor-intensive industries in Norway and Sweden, the main research question in this article is how employer hiring of temporary labor is affected by differences in national employment regulations and industries. Regarding employer motives, we find strong and similar inter-industry differences across the two countries, while the share of fixed-term employees is generally higher in Sweden than in No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 30 publications
0
24
0
2
Order By: Relevance
“…H ealth institutions in many countries suffer from nurse shortages and temporary work agencies (TWAs) have gained a foothold in this part of the labor market (Jansson & Engstrøm 2017;OECD 2015;Purcell et al 2004;Seo & Spetz 2014). Research on TWAs tend to focus on either the relationship between the client firms and TWAs in light of the client firms' need of flexible labor (see Svalund 2018) or the experiences of agency workers, such as the effects of agency work on their work-life balance, opportunities for permanent employment, or precariousness at work (De Ruyter et al 2008, Gottfried 1992Tailby 2005). However, in line with the political economy of employment relations approach, both client firms and TWAs are embedded in contingent relationships with each other and with labor and these relationships have to be understood in the political, regulatory, and economic contexts that they take place (Coe et al 2009;Jordhus-Lier et al 2015;Purcell et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…H ealth institutions in many countries suffer from nurse shortages and temporary work agencies (TWAs) have gained a foothold in this part of the labor market (Jansson & Engstrøm 2017;OECD 2015;Purcell et al 2004;Seo & Spetz 2014). Research on TWAs tend to focus on either the relationship between the client firms and TWAs in light of the client firms' need of flexible labor (see Svalund 2018) or the experiences of agency workers, such as the effects of agency work on their work-life balance, opportunities for permanent employment, or precariousness at work (De Ruyter et al 2008, Gottfried 1992Tailby 2005). However, in line with the political economy of employment relations approach, both client firms and TWAs are embedded in contingent relationships with each other and with labor and these relationships have to be understood in the political, regulatory, and economic contexts that they take place (Coe et al 2009;Jordhus-Lier et al 2015;Purcell et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…According to Srnicek (2017), platform companies are hyper-outsourced business models -in which numerical flexibility seems to be essential. Svalund et al (2018) find that companies in Sweden and Norway use a combination of atypical forms of employment in their search for a flexible workforce. Platform work might be a new addition to the menu of atypical forms of employment used by companies.…”
Section: Employer Strategies and The Institutional Contextmentioning
confidence: 96%
“…In this review of the literature, we have found seven tools commonly used for short-term flexibility in healthcare capacity management: the use of overtime, calling in temporary staff, moving staff between units, using internal staffing pools, using external staffing pools, queuing patients, and purchasing care from external providers (subcontractors). These sources are often used as reactive ad hoc solutions to fill in gaps in staff schedules [ 20 , 21 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several specialty departments share resources, which makes planning even more complex [ 16 , 17 ] and requires resource coordination at the hospital level [ 18 , 19 ]. Short-term variation in healthcare capacity is caused by, for example, sick leave, temporary leave, and vacancies, while fluctuations in demand have several explanations [ 20 , 21 ]. From a short-term perspective, managing these variations is challenging but crucial for both controlling capacity-related costs and achieving the best possible outcome for patients.…”
Section: Introductionmentioning
confidence: 99%